2017
DOI: 10.1159/000477603
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of STAT3 Signaling by Δ9-Tetrahydrocannabinol (THC) Induces Trophoblast Dysfunction

Abstract: Aims: Marijuana is a widely used illicit drug and its consumption during pregnancy has been associated with adverse reproductive outcomes. The purpose of this study was to determine the effects of chronic intake of Δ9-tetrahydrocannabinol (THC), the major component of marijuana, on trophoblast function, placental development, and birth outcomes. Methods: The pathological characteristics and distribution of cannabinoid receptors in placenta were observed by immunohistochemical (IHC) staining. Cell mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 40 publications
2
60
0
1
Order By: Relevance
“…Based on the results in this study, the reduction in fetal growth are likely attributable to impaired placental function, however, as Δ9-THC has been shown to cross the placenta, it is worth considering that Δ9-THC binding to the CB1R/CB2R in the fetal liver and brain may also have an impact 12,82,100,108 . The current study is limited in its scope and independent studies will need to be conducted to evaluate the post-natal onset of MetS along with an in-depth evaluation of the placenta vascular pathology.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Based on the results in this study, the reduction in fetal growth are likely attributable to impaired placental function, however, as Δ9-THC has been shown to cross the placenta, it is worth considering that Δ9-THC binding to the CB1R/CB2R in the fetal liver and brain may also have an impact 12,82,100,108 . The current study is limited in its scope and independent studies will need to be conducted to evaluate the post-natal onset of MetS along with an in-depth evaluation of the placenta vascular pathology.…”
Section: Discussionmentioning
confidence: 92%
“…Thus BeWo cells were cultured with and without 15 µM Δ9-THC or its inactive metabolite, 11-COOH-THC, to explore the direct effects of Δ9-THC on GLUT1 expression. 15 µM www.nature.com/scientificreports www.nature.com/scientificreports/ was chosen as the experimental dose based on studies, which determined equivalent doses to those found in the serum of cannabis users and did not affect cellular viability in BeWo cells 12,80,82,83 . Treatment with Δ9-THC led to decreases in the steady-state mRNA levels of GLUT1 and GR (p < 0.05), while the metabolite (11-COOH-THC) at an equimolar concentration, had no effect (Fig.…”
Section: δ9-thc Exposure In Human Trophoblast Results In Reduced Glutmentioning
confidence: 99%
See 3 more Smart Citations